Formation of Responsible Attitude to Health of Pre-School Children in Mountainous Terrain - Semenova, Natalia; Semenov, Oleksandr (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article discloses the aspects of work of pre-school educational establishments in terms of formation of children’s responsible attitude to their own health. The author characterizes the principles underlying the educational process. Guidelines that specify the content of teachers’ activity in mountainous terrain are given in the paper. As the result of the growth of children’s chronic diseases the author emphasizes the need to use national education experience for teaching and upbringing healthy personality of a preschooler in a mountain environment. Since clean air and aesthetic landscapes encourage active relaxation and recreation. The researcher presents the system of knowledge and skills for a healthy lifestyle which are essential for a child of preschool age. The article emphasizes the readiness of pre-school teachers and parents to use folk pedagogical means of healing, developing children's valeological knowledge and skills.